Effect of scoring first and match period in football world cup and UEFA euro - Francisco Daniel Martínez Martínez; Higinio González-García (Asociación Española de Ciencias del Deporte, 2019)
The objectives were: i) to know how the effect of scoring first affects the match result; ii) to compare the effect of scoring first, the total goals, the match scoring period and the minute of scoring the first goal (winner and loser), in the eliminatory and in the finals of both competitions (World Cup and UEFA Euro); and iii) to analyse the evolution of these variables throughout history. The sample consisted of all the matches until the year 2018 included (N = 288) in FIFA World Cup and UEFA Euro. The results showed that there were found significant differences in function of decade in World Cup in: average of total goals, average of goals in period 2 (from 15 to minute 30), average of goals in period 4 (from 45 to minute 60) and average goals in period 5 (from 60 to minute 75). Also, there were found statistically significant differences in UEFA Euro depending on the decade, in period 2 of the match. It was concluded that there is a great importance of scoring first in the UEFA Euro and World Cup. In addition, it is indicated that throughout history the 1930s, 1950s and 1970s stand out for a greater number of goals in the different variables examined.